Diverging Mobility Situations: Measuring Relative Job Accessibility and Differing Socioeconomic Conditions in New York City. (2nd January 2023) - López-García, David; Baker, Dwayne Marshall
Abstract : Recent accessibility research suggests that the relationship between time and distance in the journey to work can produce diverging mobility situations. That is, areas farther away from employment can sometimes have faster commutes than areas closer, and vice versa. This article seeks to advance such research by exploring who is likely to experience which mobility situation. With data from the Census Transportation Planning Products 2012–2016, we examine accessibility in terms of time and distance in the journey to work in New York City to assess the spatial distribution of diverging mobility situations. We conduct a series of binomial logistic regressions and multinomial logistic regression models to assess how socioeconomic characteristics influence the likelihood of experiencing a specific mobility situation while controlling for transportation infrastructure and land-use patterns. The results of our study reveal the diverging mobility patterns across New York City and highlight the importance of socioeconomic characteristics on determining diverging mobility situations.